PENENTUAN PRIORITAS PENANGANAN LAHAN KRITIS DI KABUPATEN SUKABUMI - Yanuar Argo (Pusbindiklat - LIPI, 2014)
Land degradation level can be identified by calculating Erosion Hazard Classification (EHC) and Population Pressure (PP) because these two factors are interrelated with the occurrence of land degradation. This research aims to determine the spatial distribution of management priority for degraded land using GIS based on EHC and PP with three models of scenario based on different influence of interest. The results of those three scenarios displayed that the first priority for degraded land management were located at four villages with a total area of 296.34ha. The largest village was Selajambe village, Cisaat District, Sukabumi Sub-development Area (SDA) with 132ha or 0.49% of the total research area. The second priority covered at 113 villages with a total area of 9400.69ha. Sukaraja village, Sukaraja district, Sukabumi SDA had the largest area percentage of 1.33% or 360ha of the total research area.